Desorption of furfural from bimetallic Pt-Fe oxides/alumina catalysts - Dimas Rivera, Gloria Lourdes; De la Rosa, Javier; Lucio Ortiz, Carlos J.; De los Reyes Heredia, José; González González, Virgilio Ángel; Hernández, Tomas (2014)
In this work, the desorption of furfural, which is a competitive intermediate during the production of biofuel and valuable aromatic compounds, was studied using pure alumina, as well as alumina impregnated with iron and platinum oxides both individually and in combination, using thermogravimetric analysis (TGA). The bimetallic sample exhibited the lowest desorption percentage for furfural. High-resolution transmission electron microscopy (HRTEM) imaging revealed the intimate connection between the iron and platinum oxide species on the alumina support. The mechanism of furfural desorption from the Pt-Fe/Al2O3 0.5%-0.5% sample was determined using physisorbed furfural instead of chemisorbed furfural; this mechanism involved the oxidation of the C=O group on furfural by the catalyst. The oxide nanoparticles on γ-Al2O3 support helped to stabilize the furfural molecule on the surface.